Modified zirconium oxide as well as preparation method and application thereof
Through the preparation method of modified zirconia, the problems of uneven mixing of polymer organic matter and inorganic nanozirconia and poor binding force are solved, and the gas barrier and mechanical properties of the separator for hydrogen production in alkaline electrolytic water are significantly improved.
Patent Information
- Application Number
- CN202510030787.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, when preparing a separator for hydrogen production with alkaline electrolytic water, the gas barrier and mechanical properties of the separator are poor due to uneven mixing of polymer organic matter and inorganic nanozirconia and poor binding force with the separator substrate.
Modified zirconia was obtained by mixing zirconia, additives and water, filtering and lyophilizing. The modified zirconia has a particle size of 10-60nm, which is more hydrophilic, and can mix more uniformly with polymer organic matter, improving the gas barrier and mechanical properties of the membrane.
The composite film surface resistance of modified zirconia is reduced, and the bubble point and mechanical properties are improved, which significantly improves the gas barrier and mechanical properties of the diaphragm.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of diaphragms for producing hydrogen by electrolysis of water, and specifically relates to modified zirconium oxide and a preparation method and application thereof. Background Art
[0002] Hydrogen energy, as a secondary energy source with abundant sources, green and low carbon, and wide applications, is gradually becoming one of the important carriers of global energy transformation and development. Hydrogen energy is difficult to obtain directly in large quantities from nature, and needs to rely on different technical paths and production processes for preparation. At present, the main hydrogen production paths include hydrogen production from fossil energy reforming, hydrogen production from industrial by-product gas, and hydrogen production from water electrolysis. Compared with hydrogen production from industrial by-products and fossil fuels, hydrogen production from water electrolysis can be produced by electrolyzing water with renewable electricity such as photovoltaic power generation, wind power, and hydropower. The use process can completely achieve zero carbon emissions and green hydrogen production.
[0003] There are four main technical routes for hydrogen production by water electrolysis: alkaline water electrolysis (AWE), proton exchange membrane water electrolysis (PEM), solid oxide water electrolysis (SOEC) and anion exchange membrane water electrolysis (AEM). At present, alkaline water electrolysis is the most mature technology for hydrogen production. It is easy to operate, has low investment costs, and has a long service life. It has also been put into large-scale commercial use.
[0004] As a key core component of alkaline water electrolysis hydrogen production equipment, the diaphragm mainly blocks the mixing of hydrogen and oxygen at the positive and negative electrodes of the electrolyzer, and can make the electrolyte ions migrate. Therefore, its quality determines the electrolysis energy consumption, hydrogen production purity and safety of the electrolyzer under the same catalytic electrode conditions. This requires the diaphragm to have high gas barrier properties, low resistivity and high mechanical strength. At present, the commercial diaphragms used for alkaline water electrolysis hydrogen production mainly include asbestos diaphragms, polyphenylene sulfide (PPS) diaphragms, and composite diaphragms. The asbestos diaphragms used in the early days had poor high temperature resistance and alkali corrosion resistance, poor gas barrier properties, explosion risks, and carcinogenic risks, so asbestos diaphragms were gradually eliminated. Although the high temperature resistance and alkali corrosion resistance of polyphenylene sulfide (PPS) diaphragms are better than those of asbestos diaphragms, they are still not ideal in terms of resistivity and gas barrier effects.
[0005] The organic-inorganic composite diaphragm for hydrogen production by alkaline water electrolysis consists of three parts: high molecular organic matter, inorganic nano zirconium oxide and supporting materials. It has the characteristics of both organic and inorganic materials, and has excellent gas barrier properties, ion permeability, alkali resistance and mechanical properties. In the process of preparing the diaphragm, it is necessary to first mix the high molecular organic matter and inorganic nanoparticles in a solvent to prepare a slurry for coating. However, the surface energy of zirconium oxide nanoparticles is large, and it is very easy to agglomerate, and its affinity with high molecular organic matter is poor. The slurry is very easy to have nanoparticle agglomeration, uneven mixing of organic and inorganic substances, and poor bonding between the mixed liquid and the PPS supporting material. As a result, after curing and forming the film, there are pore defects in the diaphragm and nano-ion agglomeration particles, which seriously affect the gas barrier properties and mechanical properties of the diaphragm. Summary of the invention
[0006] The present application provides a modified zirconium oxide and a preparation method and application thereof, aiming to solve the problem that when a diaphragm is prepared by using high molecular weight organic matter and inorganic nanoparticles in the prior art, the diaphragm has poor gas barrier properties and mechanical properties due to uneven mixing of the two and poor bonding with the diaphragm substrate.
[0007] In a first aspect, the present application provides a modified zirconium oxide, including zirconium oxide, additives and water;
[0008] The additives include one or more of sodium dodecyl sulfonate, sodium 1-hexane sulfonate, sodium hexanoate, sodium octanoate, n-heptylamine and N,N-dimethylhexylamine.
[0009] The modified zirconium oxide described in the present application is more hydrophilic than the unmodified zirconium oxide, and the surface resistance of the prepared composite membrane is reduced, and the bubble point and mechanical properties are improved.
[0010] According to some embodiments of the modified zirconium oxide described in the present application, the mass ratio of the zirconium oxide to the water is 1:(10-50).
[0011] According to some embodiments of the modified zirconium oxide described in the present application, the molar ratio of the zirconium oxide to the additive is 100:(0.01-0.1).
[0012] According to some embodiments of the modified zirconia described in the present application, the particle size of the modified zirconia is 10-60 nm.
[0013] The second aspect of the present application provides a method for preparing the modified zirconium oxide according to the first aspect of the present application, comprising the following steps:
[0014] (1) mixing zirconium oxide, an additive and water to obtain a reaction solution;
[0015] (2) filtering the reaction solution, and freeze-drying the solid matter obtained by filtration to obtain the modified zirconium oxide.
[0016] According to some embodiments of the method for preparing modified zirconia described in the present application, in step (1), the mixing temperature is 50-80° C., and the mixing time is 6-12 hours.
[0017] According to some embodiments of the method for preparing modified zirconium oxide described in the present application, in step (2), the freeze-drying temperature is -50°C to -70°C, and the freeze-drying time is 1-3 days.
[0018] According to some embodiments of the method for preparing modified zirconium oxide described in the present application, the method further comprises ball milling the freeze-dried product.
[0019] According to some embodiments of the method for preparing modified zirconia described in the present application, the rotation speed of the ball mill is 120-170 rpm, and the time of the ball mill is 10-30 min.
[0020] The third aspect of the present application provides a diaphragm for producing hydrogen by alkaline water electrolysis, comprising the modified zirconium oxide described in the first aspect of the present application or the modified zirconium oxide obtained by the preparation method described in the second aspect of the present application.
[0021] The diaphragm described in the present application has lower surface resistance, higher bubble point and higher mechanical properties due to the presence of the modified zirconium oxide.
[0022] According to some embodiments of the diaphragm for producing hydrogen by alkaline water electrolysis described in the present application, the diaphragm for producing hydrogen by alkaline water electrolysis also includes a polymer organic substance and a solvent.
[0023] According to some embodiments of the diaphragm for producing hydrogen by alkaline water electrolysis described in the present application, the high molecular organic matter includes one or more of polysulfone, polyethersulfone, polyvinylidene fluoride and polyphenylsulfone.
[0024] According to some embodiments of the diaphragm for producing hydrogen by alkaline water electrolysis described in the present application, the solvent includes one or more of N,N-dimethylformamide, dimethylacetamide, N-methylpyrrolidone and N-ethylpyrrolidone.
[0025] According to some embodiments of the diaphragm for producing hydrogen by alkaline water electrolysis described in the present application, the diaphragm includes the following raw materials in parts by weight: 5-15 parts of high molecular organic matter, 35-45 parts of modified zirconium oxide and 45-55 parts of solvent.
[0026] According to some embodiments of the diaphragm for producing hydrogen by alkaline water electrolysis described in the present application, the diaphragm further includes a mesh substrate layer.
[0027] According to some embodiments of the diaphragm for producing hydrogen by alkaline water electrolysis described in the present application, the mesh substrate layer includes one or more of a polyphenylene sulfide substrate layer, a polyetheretherketone substrate layer and a polytetrafluoroethylene substrate layer. DETAILED DESCRIPTION
[0028] Embodiments of the present invention are described in detail below. The embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0029] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0030] The embodiment of the present application provides a modified zirconium oxide, including zirconium oxide, additives and water;
[0031] The additives include one or more of sodium dodecyl sulfonate, sodium 1-hexane sulfonate, sodium hexanoate, sodium octanoate, n-heptylamine and N,N-dimethylhexylamine.
[0032] The modified zirconium oxide described in the present application is more hydrophilic than the unmodified zirconium oxide, and the surface resistance of the prepared composite membrane is reduced, and the bubble point and mechanical properties are improved.
[0033] In some embodiments of the present application, the mass ratio of the zirconium oxide to the water is 1:(10-50), for example, 1:10, 1:20, 1:25, 1:30, 1:40, 1:50, etc.
[0034] In some embodiments of the present application, the molar ratio of the zirconium oxide to the additive is 100:(0.01-0.1), for example, 100:0.01, 100:0.05, 100:0.08, 100:0.09, 100:0.1, etc.
[0035] In some embodiments of the present application, the particle size of the modified zirconium oxide is 10-60 nm, for example, 10 nm, 20 nm, 25 nm, 30 nm, 40 nm, 50 nm, 60 nm, etc.
[0036] The present application also provides a method for preparing the modified zirconium oxide according to the first aspect of the present application, comprising the following steps:
[0037] (1) mixing zirconium oxide, an additive and water to obtain a reaction solution;
[0038] (2) filtering the reaction solution, and freeze-drying the solid matter obtained by filtration to obtain the modified zirconium oxide. Freeze-drying can prevent the zirconium oxide from agglomerating again.
[0039] In some embodiments of the present application, in step (1), the mixing temperature is 50-80°C, such as 50°C, 60°C, 70°C, 80°C, etc., and the mixing time is 6-12 hours. This temperature range can ensure complete reaction and avoid side reactions.
[0040] In some embodiments of the present application, in step (2), the freeze-drying temperature is -50°C to -70°C, and the freeze-drying time is 1-3 days.
[0041] In some embodiments of the present application, the preparation method further comprises ball milling the freeze-dried product.
[0042] In some embodiments of the present application, the rotation speed of the ball mill is 120-170 rpm, and the time of the ball mill is 10-30 min.
[0043] The present application also provides a diaphragm for producing hydrogen by alkaline water electrolysis, comprising the modified zirconium oxide described in the first aspect of the present application or the modified zirconium oxide prepared by the preparation method described in the second aspect of the present application. The composite membrane prepared by the modified zirconium oxide has lower surface resistance, higher bubble point and mechanical properties.
[0044] The modified zirconium oxide in the diaphragm described in the present application has good dispersibility and stability, and can be mixed more evenly with high molecular organic matter to improve the affinity between the diaphragm feed liquid and the diaphragm support layer, enhance the bonding force between the feed liquid layer and the support layer, and improve the gas barrier and mechanical properties of the diaphragm.
[0045] In some embodiments of the present application, the diaphragm for producing hydrogen by alkaline water electrolysis also includes a high molecular organic matter and a solvent.
[0046] In some embodiments of the present application, the high molecular organic matter includes one or more of polysulfone, polyethersulfone, polyvinylidene fluoride and polyphenylsulfone.
[0047] In some embodiments of the present application, the solvent includes one or more of N,N-dimethylformamide, dimethylacetamide, N-methylpyrrolidone and N-ethylpyrrolidone.
[0048] In some embodiments of the present application, the diaphragm includes the following raw materials in parts by weight: 5-15 parts of high molecular organic matter, 35-45 parts of modified zirconium oxide, and 45-55 parts of solvent.
[0049] In some embodiments of the present application, the diaphragm further includes a mesh substrate layer.
[0050] In some embodiments of the present application, the mesh substrate layer includes one or more of a polyphenylene sulfide substrate layer, a polyetheretherketone substrate layer, and a polytetrafluoroethylene substrate layer.
[0051] In some embodiments of the present application, the thickness of the mesh substrate layer is 100-300 um, preferably 250-300 um.
[0052] In some embodiments of the present application, the mesh size of the mesh substrate layer is 20-100 meshes, preferably 40-60 meshes.
[0053] In some embodiments of the present application, the preparation method of the diaphragm comprises the following steps: using a solvent to dissolve a polymer organic substance and modified zirconium oxide respectively, mixing a solution containing the polymer organic substance and a solution containing modified zirconium oxide to obtain a mixed solution, and then transferring the mixed solution into a double planetary ball mill for mixing and degassing to obtain a diaphragm slurry;
[0054] The above-mentioned diaphragm slurry is coated on both sides of the diaphragm mesh substrate layer by a high-precision slit coating method. After the coating is completed, an evaporation treatment is performed. According to the pore size requirements of the diaphragm surface, the temperature range of the evaporation area is controlled to be 25-80°C, the relative humidity is 5-90%, and the residence time is 1s-2min. Then it enters the gel bath for coagulation and fixing. Pure water at 0°C-90°C or a mixture of water and solvent is used as the gel bath. As a preferred embodiment, a solution with a volume content of 30%-60% of the gel bath is used for coagulation and fixing treatment. The coagulation time is 2-15min. Finally, it is rolled up and cleaned offline.
[0055] The technical solution of the present application is further described below in conjunction with specific embodiments.
[0056] Example 1
[0057] A method for preparing modified zirconium oxide comprises the following steps:
[0058] Add zirconium oxide and water to the reactor, the volume of water is 10 times the mass of zirconium oxide, and stir quickly to form a uniform emulsion. Then add sodium dodecyl sulfate additive to the emulsion, the molar amount of the additive is 0.03% of the molar number of zirconium oxide, and after the additive is completely dissolved in water, heat it to 50°C and continue stirring for 7 hours. After the reaction is completed, use a filter press to filter, freeze-dry and filter the solid matter obtained at -55°C for 2 days, and then ball-mill to obtain a modified zirconium oxide powder with a particle size of 40-50nm.
[0059] Example 2
[0060] The only difference between Example 2 and Example 1 is that in the preparation process of the modified zirconium oxide described in Example 2, sodium hexanoate additive is used instead of sodium dodecyl sulfate additive.
[0061] The specific steps include:
[0062] Add zirconium oxide and water to the reactor, the volume of water is 10 times the mass of zirconium oxide, and stir quickly to form a uniform emulsion. Then add sodium caproate additive to the emulsion, the molar amount of the additive is 0.03% of the molar number of zirconium oxide, and after the additive is completely dissolved in water, heat it to 50°C and continue stirring for 7 hours. After the reaction is completed, use a filter press to filter, freeze-dry and filter the solid matter obtained at -55°C for 2 days, and then ball-mill to obtain a modified zirconium oxide powder with a particle size of 40-50nm.
[0063] Example 3
[0064] The only difference between Example 3 and Example 1 is that in the preparation process of the modified zirconium oxide described in Example 3, n-heptylamine additive is used instead of sodium dodecyl sulfate additive.
[0065] The specific steps include:
[0066] Add zirconium oxide and water to the reactor, the volume of water is 10 times the mass of zirconium oxide, and stir quickly to form a uniform emulsion. Then add n-heptylamine additive to the emulsion, the molar amount of the additive is 0.03% of the molar number of zirconium oxide. After the additive is completely dissolved in water, heat it to 50°C and continue stirring for 7 hours. After the reaction is completed, filter press it with a filter press, freeze-dry and filter the solid matter obtained at -55°C for 2 days, and then ball-mill it to obtain a modified zirconium oxide powder with a particle size of 40-50nm.
[0067] Example 4
[0068] The only difference between Example 4 and Example 1 is that in the preparation process of the modified zirconium oxide described in Example 4, N, N-dimethylhexylamine additive is used instead of sodium dodecyl sulfonate additive.
[0069] The specific steps include:
[0070] Add zirconium oxide and water to the reactor, the volume of water is 10 times the mass of zirconium oxide, and stir quickly to form a uniform emulsion. Then add N, N-dimethylhexylamine additive to the emulsion, the molar amount of the additive is 0.03% of the molar number of zirconium oxide, and after the additive is completely dissolved in water, heat it to 50°C and continue stirring for 7 hours. After the reaction is completed, use a filter press to filter, freeze-dry and filter the solid matter obtained at -55°C for 2 days, and then ball-mill to obtain a modified zirconium oxide powder with a particle size of 40-50nm.
[0071] Example 5
[0072] The only difference between Example 5 and Example 1 is that in the preparation process of the modified zirconium oxide described in Example 5, the molar amount of the additive added is 0.01% of the molar amount of zirconium oxide.
[0073] The specific steps include:
[0074] Add zirconium oxide and water to the reactor, the volume of water is 10 times the mass of zirconium oxide, and stir quickly to form a uniform emulsion. Then add sodium dodecyl sulfate additive to the emulsion, the molar amount of the additive is 0.01% of the molar number of zirconium oxide, and after the additive is completely dissolved in water, heat it to 50°C and continue stirring for 7 hours. After the reaction is completed, use a filter press to filter, freeze-dry and filter the solid matter obtained at -55°C for 2 days, and then ball-mill to obtain a modified zirconium oxide powder with a particle size of 40-50nm.
[0075] Example 6
[0076] The only difference between Example 6 and Example 1 is that in the preparation process of the modified zirconium oxide described in Example 6, the molar amount of the additive added is 0.05% of the molar amount of zirconium oxide.
[0077] The specific steps include:
[0078] Add zirconium oxide and water to the reactor, the volume of water is 10 times the mass of zirconium oxide, and stir quickly to form a uniform emulsion. Then add sodium dodecyl sulfate additive to the emulsion, the molar amount of the additive is 0.05% of the molar number of zirconium oxide, and after the additive is completely dissolved in water, heat it to 50°C and continue stirring for 7 hours. After the reaction is completed, use a filter press to filter, freeze-dry and filter the solid matter obtained at -55°C for 2 days, and then ball-mill to obtain a modified zirconium oxide powder with a particle size of 40-50nm.
[0079] Example 7
[0080] The only difference between Example 7 and Example 1 is that in the preparation process of the modified zirconium oxide described in Example 7, the molar amount of the additive added is 0.08% of the molar amount of zirconium oxide.
[0081] The specific steps include:
[0082] Add zirconium oxide and water to the reactor, the volume of water is 10 times the mass of zirconium oxide, and stir quickly to form a uniform emulsion. Then add sodium dodecyl sulfate additive to the emulsion, the molar amount of the additive is 0.08% of the molar number of zirconium oxide, and after the additive is completely dissolved in water, heat it to 50°C and continue stirring for 7 hours. After the reaction is completed, use a filter press to filter, freeze-dry and filter the solid matter obtained at -55°C for 2 days, and then ball-mill to obtain a modified zirconium oxide powder with a particle size of 40-50nm.
[0083] Comparative Example 1
[0084] The only difference between Comparative Example 1 and Example 1 is that, in the preparation process of the modified zirconium oxide described in Comparative Example 2, glycerol is used instead of the sodium dodecyl sulfate additive.
[0085] The specific steps include:
[0086] Add zirconium oxide and water to the reactor, the volume of water is 10 times the mass of zirconium oxide, and stir quickly to form a uniform emulsion. Then add glycerol to the emulsion, the molar amount of glycerol added is 0.03% of the molar number of zirconium oxide. After the additive is completely dissolved in water, heat it to 50°C and continue stirring for 7 hours. After the reaction is completed, use a filter press to filter, freeze-dry and filter the solid matter obtained at -55°C for 2 days, and then ball-mill to obtain a modified zirconium oxide powder with a particle size of 40-50nm.
[0087] Application Example 1
[0088] A method for preparing a diaphragm for producing hydrogen by alkaline water electrolysis comprises the following steps:
[0089] (1) Polysulfone, the modified zirconium oxide described in Example 1 and NMP in a mass ratio of 9:41:50 are uniformly mixed to obtain a membrane liquid. The membrane liquid is simultaneously coated on both sides of the PPS separator by a high-precision slit coating method, and after coating, the membrane is placed in a closed area at a temperature of 40°C and a relative humidity of 85%, and the two sides are induced to separate for 30 seconds, and then placed in a 60°C water bath for gelation for 10 minutes, and then washed with 80°C hot water for 30 minutes to obtain the desired membrane.
[0090] Application Example 2
[0091] The only difference between the diaphragm for producing hydrogen by alkaline water electrolysis described in Application Example 2 and Application Example 1 is that the modified zirconium oxide described in Example 2 is used instead of the modified zirconium oxide described in Example 1 during the preparation process of the diaphragm for producing hydrogen by alkaline water electrolysis described in Application Example 2.
[0092] Application Example 3
[0093] The only difference between the diaphragm for producing hydrogen from alkaline water electrolysis described in Application Example 3 and that in Application Example 1 is that the modified zirconium oxide described in Example 3 is used instead of the modified zirconium oxide described in Example 1 during the preparation process of the diaphragm for producing hydrogen from alkaline water electrolysis described in Application Example 3.
[0094] Application Example 4
[0095] The only difference between the diaphragm for producing hydrogen by alkaline water electrolysis described in Application Example 4 and Application Example 1 is that the modified zirconium oxide described in Example 4 is used instead of the modified zirconium oxide described in Example 1 during the preparation process of the diaphragm for producing hydrogen by alkaline water electrolysis described in Application Example 4.
[0096] Application Example 5
[0097] The only difference between the diaphragm for producing hydrogen by alkaline water electrolysis described in Application Example 5 and that in Application Example 1 is that the modified zirconium oxide described in Example 5 is used instead of the modified zirconium oxide described in Example 1 during the preparation process of the diaphragm for producing hydrogen by alkaline water electrolysis described in Application Example 5.
[0098] Application Example 6
[0099] The only difference between the diaphragm for producing hydrogen from alkaline water electrolysis described in Application Example 6 and Application Example 1 is that the modified zirconium oxide described in Example 6 is used instead of the modified zirconium oxide described in Example 1 during the preparation process of the diaphragm for producing hydrogen from alkaline water electrolysis described in Application Example 6.
[0100] Application Example 7
[0101] The only difference between the diaphragm for producing hydrogen from alkaline water electrolysis described in Application Example 7 and Application Example 1 is that the modified zirconium oxide described in Example 7 is used instead of the modified zirconium oxide described in Example 1 during the preparation process of the diaphragm for producing hydrogen from alkaline water electrolysis described in Application Example 7.
[0102] Application Example 8
[0103] The only difference between the diaphragm for producing hydrogen by alkaline water electrolysis described in Application Example 8 and Application Example 1 is that the modified zirconium oxide described in Comparative Example 1 is used instead of the modified zirconium oxide described in Example 1 during the preparation process of the diaphragm for producing hydrogen by alkaline water electrolysis described in Application Example 8.
[0104] Application Example 9
[0105] The only difference between the diaphragm for producing hydrogen by alkaline water electrolysis described in Application Example 9 and that in Application Example 1 is that ordinary zirconium oxide is used instead of the modified zirconium oxide described in Example 1 during the preparation process of the diaphragm for producing hydrogen by alkaline water electrolysis described in Application Example 9.
[0106] The performance of the diaphragm for producing hydrogen by alkaline water electrolysis described in Application Examples 1-9 of the present application is studied, and the results are shown in Table 1.
[0107] Table 1
[0108] <![CDATA[Sheet Resistance (Ω·cm 2 )]]> Bubble point (bar) Tensile strength(MPa) Puncture strength (N) Application Example 1 0.17 0.35 25.8 16.9 Application Example 2 0.18 0.25 22.7 14.1 Application Example 3 0.15 0.32 18.9 14.0 Application Example 4 0.16 0.29 21.0 18.4 Application Example 5 0.15 0.22 26.5 16.2 Application Example 6 0.19 0.27 27.5 15.5 Application Example 7 0.18 0.21 20.3 13.9 Application Example 8 0.20 0.17 17.4 10.0 Application Example 9 0.22 0.16 16.8 9.3
[0109] Note: The test method of the surface resistance described in this application refers to the national electronic industry standard SJ-T10171;
[0110] The test method for bubble point described in this application refers to GB / T 2679.14-1996;
[0111] The test method for tensile strength described in this application refers to GB / T528-2009.
[0112] It can be seen from Table 1 that the composite film prepared using modified zirconia has lower surface resistance, higher bubble point and mechanical properties than ordinary zirconia.
[0113] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.
Claims
1. A modified zirconium oxide, characterized in that: comprising zirconium oxide, additives and water; The additives include one or more of sodium dodecyl sulfonate, sodium 1-hexane sulfonate, sodium hexanoate, sodium octanoate, n-heptylamine and N,N-dimethylhexylamine.
2. The modified zirconium oxide according to claim 1, characterized in that: The mass ratio of the zirconium oxide to the water is 1:(10-50); and / or, the molar ratio of the zirconium oxide to the additive is 100:(0.01-0.1); And / or, the particle size of the modified zirconium oxide is 10-60 nm.
3. The method for preparing the modified zirconium oxide according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) mixing zirconium oxide, an additive and water to obtain a reaction solution; (2) filtering the reaction solution, and freeze-drying the solid matter obtained by filtration to obtain the modified zirconium oxide.
4. The preparation method according to claim 3, characterized in that: In step (1), the mixing temperature is 50-80° C. and the mixing time is 6-12 hours; And / or, in step (2), the freeze-drying temperature is -50°C to -70°C, and the freeze-drying time is 1-3 days.
5. The preparation method according to claim 3, characterized in that: The preparation method further comprises subjecting the freeze-dried product to ball milling; Preferably, the rotation speed of the ball mill is 120-170 rpm, and the time of the ball mill is 10-30 min.
6. A diaphragm for producing hydrogen by alkaline water electrolysis, characterized in that: The invention comprises the modified zirconium oxide according to any one of claims 1 to 2 or the modified zirconium oxide obtained by the preparation method according to any one of claims 3 to 5.
7. The diaphragm for producing hydrogen by alkaline water electrolysis according to claim 6, characterized in that: The alkaline water electrolysis hydrogen production diaphragm also includes high molecular organic matter and solvent; Preferably, the high molecular organic matter includes one or more of polysulfone, polyethersulfone, polyvinylidene fluoride and polyphenylsulfone; Preferably, the solvent includes one or more of N,N-dimethylformamide, dimethylacetamide, N-methylpyrrolidone and N-ethylpyrrolidone.
8. The diaphragm for producing hydrogen by alkaline water electrolysis according to claim 7, characterized in that: The diaphragm comprises the following raw materials in parts by weight: 5-15 parts of high molecular organic matter, 35-45 parts of modified zirconium oxide and 45-55 parts of solvent.
9. The diaphragm for producing hydrogen by alkaline water electrolysis according to claim 6, characterized in that: The separator further includes a mesh substrate layer.
10. The diaphragm for producing hydrogen by alkaline water electrolysis according to claim 6, characterized in that: The mesh substrate layer includes one or more of a polyphenylene sulfide substrate layer, a polyetheretherketone substrate layer and a polytetrafluoroethylene substrate layer.